The relationship between work and home characteristics and work engagement in medical residents - Verweij, Hanne (Perspect Med Educ, 2017)
INTRODUCTION: Work engagement is important for medical residents and the healthcare organizations they work for. However, relatively little is known about the specific predictors of work engagement in medical residents. Therefore, we examined the associations of work and home characteristics, and work-home interference with work engagement in male and female residents. METHODS: This study was conducted on a nationwide sample of medical residents. In 2005, all Dutch medical residents (n = 5245) received a self-report questionnaire. Path analysis was used to examine the associations between the potential predictors and work engagement. RESULTS: In total, 2115 (41.1%) residents completed the questionnaire. Job characteristics, home characteristics and work-home interference were associated with work engagement. Important positive contributing factors of work engagement were opportunities for job development, mental demands at work, positive work-home interference and positive home-work interference. Important negative contributing factors were emotional demands at work and negative home-work interference. The influence of these factors on work engagement was similar in male and female residents. DISCUSSION: Opportunities for job development and having challenging work are of high relevance in enhancing work engagement. Furthermore, interventions that teach how to deal skilfully with emotional demands at work and home-work interference are expected to be the most effective interventions to enhance work engagement in medical residents.